Effective Communication for Harmonious Polygamy Couple in Bone Bolango Regency - Imran Gaib; Nova Effenty Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
This study discusses effective communication for polygamy couples in Bone Bolango Regency. This research is a field research with data collection methods such as observation, interviews and documentation. The data collected is processed and analyzed with descriptive qualitative using a communication approach. The results showed that polygamists in Gorontalo Regency in living their household life remained harmonious. This is because the couple always get used to communicating effectively, so that all household problems can be resolved properly.